Vermicompost Application on Shallot (Allium cepa, L.) - Nanik Setyowati; Indra A Nugraha AR; Widodo Widodo; Zainal Muktamar (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2023)
Vermicompost is an organic fertilizer containing essential macro and micronutrients for plant growth. This study aimed to determine the dose and time of vermicompost application to the shallot. The study was carried out at an altitude of 1054 meters above sea level in Air Duku Village, Selupu Rejang District, Rejang Lebong Regency, Bengkulu Province. A Split Plot Design with three replications was used in the study. The main plot was the time of vermicompost application, which was ten days before and during planting. Sub-plots were vermicompost doses of 0, 10, 20, 30, and 40 tons/ha. Vermicompost applied ten days before planting at a 40 ton/ha resulted in the tallest shallot shoot (36.60 cm) and the highest number of leaves (28.20). Vermicompost applied ten days before planting produced more shallot bulbs (4.46 bulbs), larger bulb diameter (19.18 mm), heavier bulb weight per clump (4.75 g), and heavier bulb weight per m2 (837.73 g) than vermicompost applied at planting. Vermicompost at a dose of 40 tons/ha resulted in 5.80 bulbs per plant, 18.96 mm bulb diameter, 4.63 g bulb weight per clump, and 1022.25 g bulb weight per m2, higher than the lower dose. Therefore, vermicompost could benefit as a source of plant nutrients, comparable to synthetic fertilizers in shallot production.